2018
DOI: 10.5530/ijper.52.3.41
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality Gap Measurement in Pharmaceutical Educational Institutes: An Empirical Analysis for Model Development

Abstract: Perspective: One can observe the sea changes that have been taken place in the Indian pharmaceutical business environment. There are challenges for this section and which is possible to overcome by quality human resources. In fact, we have experienced mushroom growth of pharmaceutical education institutes (PEIs) without producing of the employable graduates. Probably this is due to poor service offerings from PEIs. Objective: Hence, the purpose of the present research to develop service quality determinants fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…36 Singh 37 has referred to the absence of quality training and research as a possible cause behind. Gupta and Mandal 38 and Mandal and Gupta 39 have also opined identically. In the global context, Hold fold and Reinders 40 have stated the need for students' judgment for offering quality service.…”
Section: Usa Information Systems Empirical Analysismentioning
confidence: 83%
See 3 more Smart Citations
“…36 Singh 37 has referred to the absence of quality training and research as a possible cause behind. Gupta and Mandal 38 and Mandal and Gupta 39 have also opined identically. In the global context, Hold fold and Reinders 40 have stated the need for students' judgment for offering quality service.…”
Section: Usa Information Systems Empirical Analysismentioning
confidence: 83%
“…Furthermore, we have reviewed five research works (Covering all most majority works available) exclu-sively to pharmaceutical education and where we have observed that only in three works authors have constructed a model for quality measurement. Even this small number of research works are heterogeneous in principle of measurement, one 39 followed perception minus expectation while Holdford et al 40,55 in two successive research works have taken a resort to performance only measure of the same. See Table 2 for a summary of the literature in relation to pharmaceutical education service quality.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is evident that the right curriculum and teaching pedagogy are crucial for an academic program. In this respect, Mandal and Gupta (2018) have opined that a course should be designed, developed and improved continuously in order to provide the students with knowledge as desired in the instructional goal.…”
Section: Academic Program Qualitymentioning
confidence: 99%